Accuracy, unbiasedness and efficiency of professional macroeconomic forecasts: An empirical comparison for the G7 - Dovern, Jonas; Weisser, Johannes (International Journal of Forecasting, 2011)
Keywords: Evaluating forecasts Macroeconomic forecasting Rationality Survey data Fixed-event forecasts

A comprehensive wealth index for cities in Germany - Dovern, Jonas; Quaas, Martin F.; Rickels, Wilfried (Ecological Indicators, 2014)
Keywords: Cities in Germany; Comprehensive wealth index

Aid and Growth Accelerations: An Alternative Approach to Assessing the Effectiveness of Aid - Dovern, Jonas; Nunnenkamp, Peter (Kyklos, 2007)

A multivariate analysis of forecast disagreement: Confronting models of disagreement with survey data - Dovern, Jonas (European Economic Review, 2015)
Keywords: Disagreement; Imperfect information; Forecast; Survey data; Macroeconomic expectation

Anchoring Inflation Expectations in Unconventional Times: Micro Evidence for the Euro Area - Dovern, Jonas; Kenny, Geoff (International Journal of Central Banking, 2020)
We exploit micro data from professional forecasters to examine the stability of the distribution of long-term inflation expectations in the euro area following the Great Recession. Although mean expectations declined somewhat, we find no evidence that the central tendency of the long-run distribution became unanchored. Also, the degree of co-movement of expectations with other variables did not increase noticeably. In contrast, long-term inflation uncertainty increased and expectations became negatively skewed. Such findings are in line with the predictions of theoretical models emphasizing the impact of the lower bound on policy rates and uncertainty about the transmission of unconventional monetary policie

Beyond fisheries: Common-pool resource problems in oceanic resources and services - Rickels, Wilfried; Dovern, Jonas; Quaas, Martin (Global Environmental Change-Human and Policy Dimensions, 2016)
Keywords: Sustainable oceanic development; Common-pool resources; Ocean health index

Disagreement among Forecasters In G7 Countries - Dovern, Jonas; Fritsche, Ulrich; Slacalek, Jiri (2009)
Using the Consensus Economics dataset with individual expert forecasts from G7 countries we investigate determinants of disagreement (cross-sectional dispersion of forecasts) about six key economic indicators. Disagreement about real variables (GDP, consumption, investment and unemployment) has a distinct dynamic from disagreement about nominal variables (inﬂation and interest rate). Disagreement about real variables intensifies strongly during recessions, including the current one (by about 40 percent in terms of the interquartile range). Disagreement about nominal variables rises with their level, has fallen after 1998 or so (by 30 percent), and is considerably lower under independent central banks (by 35 percent). Cross-sectional dispersion for both groups increases with uncertainty about the underlying actual indicators, though to a lesser extent for nominal series. Country-by-country regressions for inflation and interest rates reveal that both the level of disagreement and its sensitivity to macroeconomic variables tend to be larger in Italy, Japan and the United Kingdom, where central banks became independent only around the mid-1990s. These ﬁndings suggest that more credible monetary policy can substantially contribute to anchoring of expectations about nominal variables; its effects on disagreement about real variables are moderate.<br

Disagreement among Forecasters in G7 Countries - Dovern, Jonas; Fritsche, Ulrich; Slacalek, Jiri (Review of Economics and Statistics, 2012)

Does Joint Modelling of the World Economy Pay Off? Evaluating Global Forecasts from a Bayesian GVAR - Dovern, Jonas; Feldkircher, Martin; Huber, Florian (Journal of Economic Dynamics & Control, 2016)
Keywords: Forecast evaluation; Copula; GVAR; Global economy; Log score

Eliciting Expectation Uncertainty from Private Households - Dovern, Jonas (International Journal of Forecasting, 2024)
Recently, much attention has been devoted to measuring macroeconomic (expectation) uncertainty and its impact on aggregate economic fluctuations. This paper presents a new qualitative measure of macroeconomic expectation uncertainty based on data from a German online survey of consumer expectations. The survey design works well. Elicited expectation uncertainty is related to data volatility and conventional measures of uncertainty as expected. Its dependency on socioeconomic factors is in line with previous evidence based on quantitative uncertainty measures. The new measure offers a very efficient way of eliciting expectation uncertainty and can be used to obtain uncertainty measures on many different expectations at a low cost.<br
Keywords: acroeconomic expectations; Expectation uncertainty; Density expectations; Inflation expectation; Survey data

Estimating pass-through rates for the 2022 tax reduction on fuel prices in Germany - Dovern, Jonas; Frank, Johannes; Glas, Alexander; Müller, Lena Sophia; Perico Ortiz, Hector (Energy Economics, 2023)
We analyze the effectiveness of the German tax reduction on fuel prices (`Tankrabatt') that was introduced for three months, starting on 1 June 2022. We use the synthetic difference-in-differences estimator to compare actual retail prices of gasoline and diesel to those in a counterfactual situation without the tax reduction. For gasoline, we find that the tax reduction has been completely passed on to consumers. This result is robust to different approaches of constructing the synthetic control group. For diesel, we find evidence of at least partial pass-through, although the estimates are more sensitive to the employed specification. Moreover, the evidence suggests that pass-through rates for diesel started to decline in August while the tax reduction was still in place. <br
Keywords: fuel; gasoline; diesel; taxes; synthetic control group

Expectation Dispersion, Uncertainty, and the Reaction to News - Born, Benjamin; Dovern, Jonas; Enders, Zeno (2020)
Releases of key macroeconomic indicators are closely watched by financial markets. We investigate the role of expectation dispersion and economic uncertainty for the stock-market reaction to indicator releases. We find that the strength of the financial market response to news decreases with the preceding dispersion in expectations about the indicator value. Uncertainty, in contrast, increases the response. We rationalize our findings in a model of imperfect information. In the model, dispersion results from a perceived weak link between macroeconomic indicators and fundamentals that reduces the informational content of indicators, while higher fundamental uncertainty makes this informational content more valuable. <br
Keywords: expectation dispersion; uncertainty; macroeconomic news; stock market; event study; forecaster disagreement

Expectation dispersion, uncertainty, and the reaction to news - Born, Benjamin; Dovern, Jonas; Enders, Zeno (European Economic Review, 2023)
Key macroeconomic indicator releases are closely monitored by financial markets. We examine the impact of expectation dispersion and economic uncertainty on the stock market’s reaction to these indicators. We find that the strength of the financial market response to news decreases with the preceding dispersion in expectations about the indicator value. Higher uncertainty, in contrast, increases the response. We rationalize our findings in a model of imperfect information. In the model, dispersion results from a perceived weak link between macroeconomic indicators and fundamentals that reduces the informational content of indicators, while fundamental uncertainty makes their informational content more valuable.<br
Keywords: Expectation dispersion; uncertainty; macroeconomic news; stock market; event study; forecaster dispersion

Firm-Level Expectations and Behavior in Response to the Covid-19 Crisis - Dovern, Jonas; Buchheim, Lukas; Krolage, Carla; Link, Sebastian (2020)
This paper studies the determinants of firms’ business outlook and managerial mitigation strategies in the wake of the Covid-19 crisis using a representative panel of German firms. We first demonstrate that the crisis amplifies pre-crisis weaknesses: Firms that appear relatively weak before the crisis are harder hit initially, and, on top of the initial impact, expect more difficulties for their businesses going forward. Consequently, such firms are first to cut employment and investment. Second, our results highlight that expectations regarding the duration of the shutdown—which, at this point of the crisis, exhibit plausibly random variation—are an important determinant of the chosen mitigation strategies: Firms that expect the shutdown to last longer are more likely to lay off workers and to cancel or postpone investment project
Keywords: expectations; firm behaviour; Covid-19; shutdown; employment; investment

Forecast performance, disagreement, and heterogeneous signal-to-noise ratios - Dovern, Jonas; Hartmann, Matthias (Empirical Economics, 2017)
Keywords: Disagreement; Imperfect information; Expectations; Signal-to-noise ratio

Global prediction of recessions - Dovern, Jonas; Huber, Florian (Economics letters, 2015)
Keywords: Probability forecast; GVAR; Recession forecast; QPS

How Do Firms Form Expectations of Aggregate Growth? New Evidence from a Large-Scale Business Survey - Dovern, Jonas; Müller, Lena Sophia; Wohlrabe, Klaus (2020)
Expectations are highly relevant for macroeconomic dynamics. Yet, the empirical evidence about properties of corporate macroeconomic expectations is scarce. Using new survey data on quantitative growth expectations of firms in Germany, we show that expectations are highly dispersed. The degree of dispersion depends on firm size and on how important the general economy is for the business of firms, supporting theories of rational inattention. Firms seem to extrapolate from local economic conditions and business experiences to aggregate growth expectations. Differences in growth expectations are associated with differences in firms’ investment and labor deman
Keywords: GDP expectations; expectation heterogeneity; firm; ifo business tendency survey

How Economic Crises Damage Potential Output – Evidence from the Great Recession - Dovern, Jonas; Zuber, Christopher (Journal of Macroeconomics, 2020)
Economic crises lead to lower potential output (PO) estimates, but little is known about which components of PO are revised. Our paper answers the questions of how much, how fast, and how persistently estimates of the capital stock, of trend labor, and of trend total factor productivity are revised downwards after major economic crises. It shows that revisions to different components of PO contributed equally to the substantial overall decline in estimated PO levels. Revisions of trend labor are predominantly driven by revisions of the NAWRU. The heterogeneity of revisions across EU countries after the Great Recession is large, suggesting that different policies are needed to bring countries back to their previous growth path
Keywords: Potential output Trend Output gap Great Recession European Commission

How resilient is the German banking system to macroeconomic shocks - Dovern, Jonas; Meier, Carsten-Patrick; Vilsmeier, Johannes (Journal of Banking & Finance, 2010)
Keywords: Stress testing Banking VAR Financial stability

Indicators for monitoring sustainable development goals: An application to oceanic development in the European Union - Rickels, Wilfried; Dovern, Jonas; Hoffmann, Julia; Quaas, Martin F.; Schmidt, Joern O.; Visbeck, Martin (Earth's Future, 2016)
Keywords: Sustainable Development Goals; Composite Indicators; Ocean; Indicator Selection

Information rigidities: Comparing average and individual forecasts for a large international panel - Dovern, Jonas; Fritsche, Ulrich; Loungani, Prakash; Tamirisa, Natalia (International Journal of Forecasting, 2015)
Keywords: Aggregation bias; Growth forecasts; Forecast behavior; Rational inattention; Information rigidity

Information Rigidities in Economic Growth Forecasts: Evidence from a Large International Panel - Dovern, Jonas; Fritsche, Ulrich; Tamirisa, Natalia; Loungani, Prakash (2013)
We examine the behavior of forecasts for real GDP growth using a large panel of individual forecasts from 30 advanced and emerging economies during 1989–2010. Our main findings are as follows. First, our evidence does not support the validity of the sticky information model (Mankiw and Reis, 2002) for describing the dynamics of professional growth forecasts. Instead, the empirical evidence is more in line with implications of noisy information models (Woodford, 2002; Sims, 2003). Second, we find that information rigidities are more pronounced in emerging economies than advanced economies. Third, there is evidence of nonlinearities in forecast smoothing. It is less pronounced in the tails of the distribution of individual forecast revisions than in the central part of the distribution. <br

International transmission and business-cycle effects of financial stress - Dovern, Jonas; Van Roye, Bjoern (Journal of Financial Stability, 2014)
Keywords: Financial crises; Financial stress; Financial spillovers; Macro-financial linkages; Global VAR

Large-Scale Intentional Interventions into the Climate System? Assessing the Climate Engineering Debate - Dovern, Jonas; Rickels, Wilfried; Klepper, G. (Report for the German Federal Ministry of Education and Research, Kiel, December 2011, 2011)

Local Information and Firm Expectations about Aggregates - Dovern, Jonas; Müller, Lena; Wohlrabe, Klaus (Journal of Monetary Economics, 2023)
Using new survey data on quantitative growth expectations of firms in Germany, we show that firms resort to local information when forming expectations about aggregate growth. Firms extrapolate from the economic situation in their county, industry growth and their individual business situation. Variables (fixed effects) measuring local signals account for up to 26 % (47 %) of the expectation dispersion across firms. The effect is particularly strong for small firms. Our results confirm predictions of theoretical models with rational inattentio
Keywords: GDP expectations; expectation heterogeneity; disagreement; rational inattention; ifo business tendency survey

Mind the Naive Forecast! A Rigorous Evaluation of Forecasting Models for Time Series with Low Predictability - Beck, Nico; Dovern, Jonas; Vogl, Stefanie (Applied Intelligence, 2025)
In the field of time series forecasting, numerous machine learning studies have assessed the performance of new methods on highly volatile data from macroeconomics and finance. Unlike in other domains, where models are also compared to simpler statistical or naive baselines, they mostly compare the performance solely relative to other complex models. This approach may lead to limited conclusions and reduce the practical significance of the results, as it overlooks the unpredictability of some highly volatile time series in the datasets used. We apply state-of-the-art methods from time-series econometrics and machine learning, including autoregressive integrated moving average (ARIMA), exponential smoothing (ETS), Bayesian vector autoregressive model (BVAR), long-short term memory neural networks (LSTM), historical consistent neural networks (HCNN), deep vector autoregressive neural networks (DeepVAR), temporal fusion transformers (TFT), and extreme gradient boosting (XGBoost). Our results demonstrate that no method consistently outperforms the naive (no-change) forecast for highly volatile time series from two popular datasets containing exchange rates and stock prices, rendering comparative analysis between complex models less meaningful. In contrast, when applied to more predictable macroeconomic price indices, many of the methods significantly outperform naive forecasts. We find that the performance of machine learning models deteriorates more than that of statistical models for high-volatility time series. This study highlights the critical importance of using appropriate benchmark models, including cost-effective, simple approaches, on datasets that permit meaningful conclusion
Keywords: Time series; Benchmark; Forecasting methods; Naive benchmark; No-Change; Random walk

Order-Invariant Tests for Proper Calibration of Multivariate Density Forecasts - Dovern, Jonas; Manner, Hans (Journal of Applied Econometrics, 2020)
Established tests for proper calibration of multivariate density forecasts based on Rosenblatt probability integral transforms can be manipulated by changing the order of variables in the forecasting model. We derive order invariant tests. The new tests are applicable to densities of arbitrary dimensions and can deal with parameter estimation uncertainty and dynamic misspecification. Monte Carlo simulations show that they often have superior power relative to established approaches. We use the tests to evaluate GARCH-based multivariate density forecasts for a vector of stock market returns and macroeconomic forecasts from a BVAR with time-varying parameter
Keywords: density calibration; goodness-of-fit test; predictive density; Rosenblatt transformation

Recessions and Potential Output: Disentangling Measurement Errors, Supply Shocks, and Hysteresis Effects - Dovern, Jonas; Zuber, Christopher (Scandinavian Journal of Economics, 2020)
This paper investigates expert revisions of potential output (PO) estimates following recessions. Using data from the Organisation for Economic Co‐operation and Development (OECD), we show that downward revisions are substantial, permanent, and mostly driven by supply shocks. In contrast, PO estimates do not significantly react to demand shocks. Revisions are also partly caused by mismeasurement of PO before recessions. In particular, we show that the length of the preceding boom and pre‐recession values of the current account balance and credit volumes are correlated with post‐recession PO revisions. Our results call for improved methods for estimating PO and provide evidence against the existence of substantial hysteresis following demand shock
Keywords: Hysteresis; OECD; output gap; potential output; trend

Sentiment and Firm Behavior During the COVID-19 Pandemic - Buchheim, Lukas; Dovern, Jonas; Krolage, Carla; Link, Sebastian (Journal of Economic Behavior & Organization, 2022)
How did optimism or pessimism about the duration of shutdowns during the COVID-19 pandemic aﬀect ﬁrms’ business outlook and behavior? In a large panel of German ﬁrms, we identify sentiment as the only plausible determinant of the cross-sectional variation in the expected shutdown length because this variation is uncorrelated with fundamentals. Firms incorporate this sentiment regarding the shutdown duration in their more general business outlook. Sentiment was also an important determinant of ﬁrms’ crisis response: More pessimistic ﬁrms—those that perceived the shutdown to last longer—were more likely to implement strong measures like layoﬀs or canceling investments. The implementation of soft measures, e.g., working from home, was unrelated to the sentiment regarding the shutdown length.<br
Keywords: Sentiment; ﬁrm behavior; COVID-19; shutdown; employment; investment

Sticky Information Phillips Curves: European Evidence - Dovern, Jonas; Fritsche, Ulrich; Slacalek, Jiri; Döpke, Jörg (2008)
We estimate the sticky information Phillips curve model of Mankiw and Reis (2002) using survey expectations of professional forecasters from four major European economies. Our estimates imply that inflation expectations in France, Germany and the United Kingdom are updated about once a year, in Italy about once each six months.<br

Systematic errors in growth expectations over the business cycle - Dovern, Jonas; Jannsen, Nils (International Journal of Forecasting, 2017)
Keywords: Forecasting; Forecast bias; Macroeconomic expectations; Growth expectation; Survey data

Testing for Differences in Survey-Based Density Expectations: a Compositional Data Approach - Dovern, Jonas; Glas, Alexander; Kenny, Geoff (Journal of Applied Econometrics, 2024)
We propose to treat survey-based density expectations as compositional data when testing either for heterogeneity in density forecasts across different groups of agents or for changes over time. Monte Carlo simulations show that the proposed test has more power relative to both a bootstrap approach based on the KLIC and an approach which involves multiple testing for differences of individual parts of the density. In addition, the test is computationally much faster than the KLIC-based one, which relies on simulations, and allows for comparisons across multiple groups. Using density expectations from the ECB Survey of Professional Forecasters and the U.S. Survey of Consumer Expectations, we show the usefulness of the test in detecting possible changes in density expectations over time and across different types of forecasters.<br
Keywords: compositional data; density forecasts; survey forecasts; disagreement

The Dynamics of European Inflation Expectations - Dovern, Jonas; Döpke, Jörg; Fritsche, Ulrich; Slacalek, Jiri (The B.E. Journal of Macroeconomics, 2008)

The Long-term Distribution of Expected Inflation in the Euro Area: What Has Changed since the Great Recession? - Dovern, Jonas; Kenny, Geoff (2017)
This paper analyses the distribution of long-term inflation expectations in the euro area using individual density forecasts from the ECB Survey of Professional Forecasters. We exploit the panel dimension in this dataset to examine whether this distribution became less stable following the Great Recession, subsequent sovereign debt crisis and period when the lower bound on nominal interest rates became binding. Our results suggest that the distribution did change along several dimensions. We document a small downward shift in mean long-run expectations toward the end of our sample although they remain aligned with the ECB definition of price stability. More notably, however, we identify a trend toward a more uncertain and negatively skewed distribution with higher tail risk. Another main finding is that key features of the distribution are influenced by macroeconomic news, including the ex post historical track record of the central bank. <br

The Sticky Information Phillips Curve. European Evidence - Dovern, Jonas; Döpke, Jörg; Fritsche, Ulrich; Slacalek, Jiri (Journal of Money, Credit and Banking, 2008)

What macroeconomic shocks affect the German banking system? Analysis in an integrated micro‐macro model - Dovern, Jonas; Blank, Sven (Journal of Financial Economic Policy, 2010)

When are GDP forecasts updated? Evidence from a large international panel - Dovern, Jonas (Economics letters, 2013)

Zur Reaktion von Unternehmen auf die Coronakrise: Welche Rolle spielen die erwartete Krisendauer und die Geschäftslage vor der Krise? - Buchheim, Lukas; Dovern, Jonas; Krolage, Carla; Link, Sebastian (2020)
Zur Bekämpfung der Corona-Pandemie wurde die Wirtschaftstätigkeit in weiten Teilen der deutschen Volkswirtschaft in erheblichem Maße heruntergefahren. Diese Studie untersucht mithilfe der Daten aus der ifo Konjunkturumfrage, wie deutsche Unternehmen im Zuge dieses partiellen Shutdown ihre Erwartungen angepasst und welche Maßnahmen sie ergriffen haben. Wir zeigen zunächst, dass die Krise bestehende Schwierigkeiten verstärkt: Unternehmen, die bereits vor der Krise in einer schlechten Lage waren, sind von dieser stärker betroffen und erwarten zukünftig zusätzliche Probleme für ihre Unternehmen. Folglich bauen solche Unternehmen überdurchschnittlich häufig Arbeitsplätze ab und streichen Investitionen. Die Erwartungen hinsichtlich der Krisendauer sind ebenfalls eine wichtige Determinante der getroffenen Maßnahmen: Unternehmen, die erwarten, dass die krisenbedingten Einschränkungen des öffentlichen Lebens mindestens vier Monate anhalten werden, bauen deutlich häufiger Beschäftigung ab bzw. stornieren oder verschieben Investitionsprojekte als Firmen, die von einer schnellen Aufhebung der Restriktionen ausgehe